Preparation method of photoelectrochemical sensor for detecting and degrading tetracycline

The self-powered photoelectrochemical sensor built with CuBi2O4/MoSe2 heterostructure solves the problems of low sensitivity and high cost of tetracycline detection and degradation in traditional methods, and achieves efficient, stable and selective detection and degradation effects.

CN120577376APending Publication Date: 2025-09-02ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510718950.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The prior art has problems of low sensitivity, poor selectivity and high cost when detecting and degrading tetracycline contaminants in aquatic systems. Traditional methods require expensive instruments and skilled operators, and it is difficult to achieve efficient real-time monitoring and degradation.

Method used

A self-powered photoelectrochemical sensor is built using CuBi2O4/MoSe2 heterostructure to achieve synchronous detection and photocatalytic degradation of tetracycline through photoelectrochemical reactions. The carrier concentration gradient of heterojunction and the built-in electric field are used to accelerate the separation of photogenerated electron-hole pairs, and improve the photoelectric conversion efficiency.

Benefits of technology

It realizes tetracycline detection with high sensitivity, fast response, good stability and high selectivity, with a degradation rate of 93%, and the sensor can be reused, with high degradation efficiency and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120577376A_ABST
    Figure CN120577376A_ABST
Patent Text Reader

Abstract

According to the self-powered photoelectrochemical sensor for tetracycline sensitive detection and degradation, firstly, a CuBi2O4 / MoSe2 heterojunction with good photoelectric response is successfully prepared by adopting an in-situ generation method, and relatively strong and stable initial photocurrent is generated; under optimized experimental conditions, the linear range of the sensor is 1nM-10uM, the detection limit is 0.2 nM, and meanwhile, the degradation rate of the sensor to tetracycline within 30min reaches 93%. The photoelectrochemical sensor shows excellent stability, high response speed, high selectivity and good detection reproducibility. According to the invention, a synergistic effect of a detection signal and a photocatalytic degradation function is realized through integrated design, an innovative strategy is provided for real-time monitoring and synchronous efficient degradation of tetracycline pollutants, and development of a photoelectric detection-catalytic degradation integrated platform and innovative application of the photoelectric detection-catalytic degradation integrated platform in the field of environmental governance are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] 1. Name

[0002] A method for preparing a photoelectrochemical sensor for detecting and degrading tetracycline Technical Field

[0003] This paper describes a self-powered photoelectrochemical platform based on a CuBi2O4 / MoSe2 heterojunction, enabling simultaneous detection and photocatalytic degradation of tetracycline in an electrolyte. This integrated system, which operates via a photocurrent response, has advanced environmental monitoring and remediation technologies and holds promising applications in environmental protection. Background Art

[0004] Tetracycline contamination in aquatic systems can pose serious ecological and public health risks, leading to widespread antibiotic resistance and persistent toxicity to biota. Therefore, the management of antibiotic-containing wastewater has become a critical issue in environmental protection. To monitor these pollutants, various analytical methods have been developed for trace detection of tetracyclines. Traditional techniques, such as high-performance liquid chromatography, offer high precision but require expensive instrumentation and skilled operators. Colorimetric analysis and fluorescence spectroscopy, while simple to operate, have limitations in sensitivity and anti-interference capabilities. Therefore, the development of a highly sensitive and specific tetracycline assay is crucial.

[0005] Photoelectrochemical sensing technology, as an emerging detection method, has attracted widespread attention due to its unique advantages. It organically combines photoexcitation with electrochemical detection, achieving sensitive detection of target substances through photoelectric conversion. Its principle is that when photoactive materials are exposed to light, electron-hole pairs are generated. These photogenerated carriers participate in redox reactions at the electrode / electrolyte interface, generating a detectable photoelectric signal. By analyzing the characteristics of signal changes, the target substance can be qualitatively identified and quantitatively detected. Compared with traditional methods, this technology has significant advantages such as high sensitivity, good selectivity, and rapid response.

[0006] Combining CuBi2O4 with MoSe2 to form a type II heterojunction creates a carrier concentration gradient, promoting interfacial charge transfer. Simultaneously, the built-in electric field accelerates the separation of photogenerated electron-hole pairs and suppresses charge recombination. This synergistic effect significantly improves photoelectric conversion efficiency. Using this heterojunction, a self-powered photoelectrochemical sensor was constructed for the detection and degradation of tetracycline. The resulting self-powered photoelectrochemical sensor exhibits excellent properties, including fast response, high sensitivity, strong specificity, excellent stability, and reusability. It holds promise as a platform for real-time monitoring and degradation of pollutants in environmental remediation. Summary of the Invention

[0007] The present invention provides a method for preparing a novel self-powered photoelectrochemical sensor. This sensor, which does not require an external power source, can simultaneously achieve real-time detection and efficient photocatalytic degradation of tetracycline, offering significant technical advantages.

[0008] The purpose of the present invention is achieved by the following technical solutions:

[0009] 1. A method for preparing a photoelectrochemical sensor for tetracycline detection and degradation, comprising the following steps:

[0010] (1) Preparation of CuBi2O4 / MoSe2 heterojunction composite materials;

[0011] First, Bi(NO3)3.5H2O and Cu(NO3)2.3H2O were dissolved in deionized water and magnetically stirred to completely dissolve them. An appropriate amount of NaOH was added to adjust the pH to 10. Then, MoSe2 was added separately while magnetically stirring. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and reacted at a certain temperature for a period of time. After natural cooling, the product was washed with ultrapure water and anhydrous ethanol multiple times, dried, and placed in a sample tube for later use.

[0012] (2) Pretreatment of ITO electrode: Clean the ITO conductive glass with acetone, ethanol and deionized water in sequence.

[0013] (3) CuBi2O4 / MoSe2 suspension was added dropwise onto the conductive surface of ITO conductive glass and dried naturally at room temperature; an ITO electrode for detecting and degrading tetracycline was prepared, and finally a photoelectrochemical sensor was obtained.

[0014] In step (1), the ratio of bismuth nitrate pentahydrate, copper nitrate trihydrate and molybdenum selenide is 0.012g:0.003g:0.068g; the mixed solution is reacted in an oven at 180°C for 12 hours, and the precipitate is taken out and washed three times with deionized water and anhydrous ethanol respectively, and finally dried in a vacuum oven at 60°C for 6 hours.

[0015] In step (2), the size of the ITO conductive glass is: 20 * 10 * 1.1mm, and each ultrasonic time is 15min to fully remove the oxide on the ITO surface.

[0016] In step (3), a hole with a diameter of 6 mm is punched on a 1 cm × 1 cm insulating tape with a hole puncher, and the hole is covered with the upper half of the conductive surface of the cleaned ITO electrode sheet. Then, 20 μL of the evenly dispersed CuBi2O4 / MoSe2 suspension is dropped into the 6 mm hole of the insulating tape, and the CuBi2O4 / MoSe2 / ITO electrode sheet is obtained by natural air drying.

[0017] 2. The detection and degradation steps of a photoelectrochemical sensor for detecting tetracycline are as follows:

[0018] (1) Performance testing was performed using a standard three-electrode electrochemical workstation system, and Na2SO4 was selected as the experimental electrolyte.

[0019] (2) A self-made programmable mobile platform is used to control the light switch, and the light source is turned on and off every 20 seconds. No external voltage is required during the test.

[0020] (3) Record the photoelectric response changes of the ITO working electrode in the blank control and when adding different concentrations of tetracycline as the analyte and draw the fitting curve for analysis.

[0021] (4) Based on the above experiments, different CuBi2O4 / MoSe2 / ITO electrodes from the same batch were selected for photoelectric performance testing to analyze the performance gap between different ITO electrodes.

[0022] (5) Adding different interfering substances to the electrolyte, recording the photoelectric response changes of the CuBi2O4 / MoSe2 / ITO electrode, and comparing them with the photoelectric response changes when tetracycline was added recorded in step (4).

[0023] (6) Tetracycline was added to the electrolyte and the light was continuously irradiated for 30 minutes to observe the corresponding photoelectric response changes.

[0024] In step (1), the system used a Shanghai Chenhua CHI 660E model, with an external xenon lamp as the excitation source. A silver / silver chloride electrode was used as the reference electrode, a platinum wire electrode was used as the counter electrode, and the prepared CuBi2O4 / MoSe2 / ITO was used as the working electrode. A unified experimental environment was used, and sensor performance tests were performed using 50 ml of 0.1 M Na2SO4 containing 0.1 M ascorbic acid as the experimental electrolyte. All experiments were conducted at room temperature (25°C).

[0025] In step (2), the wavelength band of sunlight simulated by the xenon lamp is 200nm-1100nm.

[0026] In step (3), the stability of the ITO electrode is tested, and the electrochemical workstation test time is more than 1000s.

[0027] In step (4), the concentration range of tetracycline to be detected is: 1nm-10um.

[0028] In step (5), in order to ensure that sufficient data is collected, generally at least 5 ITO electrodes from the same batch are selected for experimental testing.

[0029] In step (6), in order to test the high selectivity of the photoelectrochemical sensor for tetracycline detection, the concentration of the added interfering substance is generally 10 times or more of the selected concentration of tetracycline.

[0030] In step (7), in order to test the degradation performance of the photoelectrochemical sensor on tetracycline, the change in tetracycline concentration is verified by recording the change in current.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. This invention introduces a one-step hydrothermal method for preparing composite materials for photoelectrochemical sensors. This method reduces the number of preparation steps, enabling low-cost, high-efficiency synthesis of composite materials while facilitating adjustment and optimization of experimental tests.

[0033] 2. This experiment used an in-situ generation method to successfully construct a pn-type heterojunction by combining copper bismuthate and molybdenum diselenide, forming a carrier concentration gradient and driving interfacial charge transfer. Its built-in electric field accelerates the separation of photogenerated electron-hole pairs, inhibits recombination, and significantly improves the photoelectric conversion efficiency.

[0034] 3. The photoelectrochemical sensor constructed by the present invention for tetracycline detection and degradation has a linear range of 1nM-10uM and a detection limit of 0.2nM. At the same time, the degradation rate of tetracycline by the sensor reaches 93% within 30 minutes. The photoelectrochemical sensor exhibits excellent stability, fast response speed, high selectivity and good detection reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an IT curve diagram of the CuBi2O4 / MoSe2 composite material of the present invention at different concentrations at 0V bias.

[0036] Figure 2 This is the IT diagram of the stability experiment of the CuBi2O4 / MoSe2 photoelectrochemical photoelectric sensor of the present invention under 0V bias.

[0037] Figure 3 This is the IT diagram of the CuBi2O4 / MoSe2 photoelectrochemical photoelectric sensor of the present invention implemented at 0V bias for 7 days of stability experiment

[0038] Figure 4 The photocurrent response change diagram of the prepared photoelectrochemical sensing system under different tetracycline concentrations and the linear fitting curve diagram of the photocurrent response changing with the tetracycline concentration.

[0039] Figure 5 The photocurrent response change diagram of the prepared photoelectrochemical sensing system under tetracycline concentration and the corresponding tetracycline concentration change diagram.

[0040] Figure 6 This is a comparison chart of the photocurrent response changes of the photoelectrochemical sensing system prepared in Example 1 to 2uM different interferents and 200nM tetracycline, as well as a performance difference analysis chart between different finished products of the same batch.

[0041] Specific implementation

[0042] The present invention will be further explained below with reference to specific examples and accompanying drawings. DETAILED DESCRIPTION

[0043] To better understand the present invention, embodiments thereof will be described in detail below with reference to the accompanying drawings. These embodiments are based on the technical solutions of the present invention and provide detailed implementation steps. It should be noted that the following description is merely illustrative and is intended to further illustrate the present invention, rather than to limit it.

[0044] Experimental conditions not specified in the examples generally followed conventional conditions or those recommended by the reagent companies. Unless otherwise specified, the reagents and consumables used in the examples were all available through conventional commercial channels.

[0045] Example 1:

[0046] This embodiment provides a method for preparing a photoelectrochemical photoelectric sensor, comprising the following steps:

[0047] (1) Preparation of CuBi2O4 / MoSe2 heterojunction composite materials:

[0048] First, 1 mmol of sodium molybdate and 2 mmol of selenium powder were dissolved in 30 mL of deionized water. An appropriate amount of citric acid was added, and the solution was stirred and ultrasonicated for 10 minutes. Finally, the homogeneous solution was transferred to a sealed autoclave and heated at 180°C for 18 hours. The mixture was then centrifuged, washed, and dried to obtain MoSe2. Next, Bi(NO3)3·5H2O and Cu(NO3)2·3H2O were dissolved in deionized water and magnetically stirred until completely dissolved. An appropriate amount of NaOH was added to adjust the pH to 10. Subsequently, MoSe2 was added while magnetically stirring. The mixture was transferred to a Teflon-lined autoclave and reacted at a constant temperature for a period of time. After cooling, the solution was transferred to a Teflon-lined autoclave and reacted at 180°C for 12 hours. After the reaction is completed, the high-temperature reactor is cooled to room temperature, and the solution in the polytetrafluoroethylene liner is taken out and centrifuged at 8000 rpm using a centrifuge. The solution is washed alternately with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven and dried for 6 hours to finally obtain a CuBi2O4 / MoSe2 heterojunction composite material.

[0049] (2) Preparation of CuBi2O4 / MoSe2 / ITO electrode:

[0050] The ITO conductive glass was cleaned sequentially with acetone, ethanol, and deionized water. This cleaning process was intended to remove any oxidized material on the glass surface. A 6mm diameter hole was then punched in a 1cm x 1cm piece of insulating tape. This hole was then placed over the top half of the cleaned conductive surface of the ITO electrode. 20μL of a well-dispersed CuBi2O4 / MoSe2 suspension was then dripped into the 6mm hole in the tape. The film was then air-dried to obtain the CuBi2O4 / MoSe2 / ITO electrode.

[0051] (3) Photoelectric response performance test:

[0052] For electrochemical testing of the CuBi2O4 / MoSe2 / ITO electrode sheets, a standard three-electrode electrochemical workstation system was used. 0.1M Na2SO4 and 0.1M ascorbic acid were selected as the electrolyte solution, and the system was a Shanghai Chenhua CHI660 E model. The reference electrode used in this system was an Ag / AgCl electrode, while the counter electrode was a platinum wire electrode. To provide illumination for the photoelectrochemical measurements, a Solar-500W external xenon lamp was used as the light source. All electrochemical experiments were conducted at room temperature, with a custom-made programmable motion stage controlling the light switch, which turned the light source on and off every 20 seconds. No external voltage was required during the tests.

[0053] The following is an explanation of the accompanying drawings of Example 1 of the present invention:

[0054] Figure 1 The following plots the IT curves of the CuBi2O4 / MoSe2 composite material synthesized according to the present invention at different concentration ratios. Overall, a concentration of 6 mg / ml exhibits higher photocurrent density, more stable response, and faster photoelectric response time. These results indicate that at this concentration, the heterojunction interface is more conducive to the separation and transport of photogenerated carriers, achieving an optimal balance between carrier separation and transport, effectively improving photoresponse and achieving higher photoelectric conversion performance.

[0055] from Figure 2 As can be seen from the graph, after an 800-second on-off cycle, the photocurrent signal remained essentially stable throughout the test, showing no significant fluctuations or attenuation. Further calculations revealed a photocurrent loss rate of 6%, demonstrating the sensor's excellent resistance to photocorrosion and stable photoelectric response.

[0056] from Figure 3It can be seen that in order to further evaluate its storage stability, the prepared sensor was stored under standard room temperature conditions for 7 days and then retested. It was found that its photocurrent response only decayed by 10%. This excellent long-term stability is due to the good structural stability of the heterojunction material.

[0057] from Figure 4 It can be seen that within the tetracycline concentration range of 1nM to 10μM, the photocurrent signal shows a regular decreasing trend with increasing concentration, indicating that the tetracycline molecules have a specific interaction with the photoelectrode surface, effectively inhibiting the separation and transmission process of photogenerated carriers. Further analysis of the test results found that the photocurrent response value (I) and the logarithm of the tetracycline concentration showed a good linear relationship. The linear regression equation obtained by least squares fitting was I (uA) = 0.12lgC (nM) - 0.99, and the correlation coefficient R 2 =0.99, indicating that the sensor has excellent quantitative analysis capability, and the calculated detection limit is as low as 0.2 nM. This shows that the sensor exhibits a wide linear range and low detection limit.

[0058] from Figure 5 The degradation performance of the photoelectrochemical sensor can be seen. By testing the change of tetracycline concentration at different times, the degradation of the sensor is analyzed in real time, corresponding to the change of photocurrent response at different time periods. The figure shows that the photocurrent signal increases with time. Substituting the current into the above linear regression equation, the corresponding change of tetracycline concentration can be obtained. It can be seen that the tetracycline concentration increases from 10 to 10 within 30 minutes. 4 uM is reduced to 10 2.79 uM, and the real-time degradation rate was calculated to be 93%, indicating that the sensor has significant high efficiency and fast response characteristics.

[0059] from Figure 6 It can be seen that in order to evaluate the specificity of CuBi2O4 / MoSe2 / ITO sensor, we selected seven common interfering substances for specificity testing, including inorganic ions (Cd + 、Cl-、NO3 - , K + Br -), small biological molecules (glutathione, glucose), when tested under the condition that the interfering substance concentration (2μM) is 10 times that of tetracycline detection concentration (200nM), only tetracycline can cause significant changes in the photocurrent signal, while the photocurrent changes caused by other interfering substances are significantly smaller than the effect of tetracycline. This result fully proves that the developed photoelectrochemical sensor has a highly specific recognition ability for tetracycline molecules. In order to further verify the repeatability of the CuBi2O4 / MoSe2 / ITO heterojunction sensor, we conducted the same test on heterojunction electrode sheets prepared from eight different batches. Through statistical analysis of the experimental data, the calculated relative standard deviation was 4.15%, which proves that the sensor has excellent preparation reproducibility and detection reliability.

[0060] Note: The preferred embodiments described above are intended only to illustrate the present invention and should not be construed as limiting the scope of the present invention. Those skilled in the art will appreciate that modifications or reasonable substitutions may be made to the present invention without departing from the scope of the present invention, and all such modifications and substitutions fall within the scope of protection of the present invention.

Claims

1. A self-powered photoelectrochemical sensor for detecting and degrading tetracycline, characterized in that: The method includes a CuBi2O4 / MoSe2 composite material as a working electrode, an Ag / AgCl reference electrode, a platinum wire counter electrode, and tetracycline as a substance to be tested.

2. A self-powered photoelectrochemical sensor for detecting and degrading tetracycline according to claim 1, characterized in that: Take 20μL of evenly dispersed CuBi2O4 / MoSe2 suspension and drop it onto ITO conductive glass. Finally, let it air-dry to obtain a CuBi2O4 / MoSe2 / ITO electrode sheet. The prepared electrode sheet is fixed on a platinum electrode holder as the working electrode in the three-electrode system. Tetracycline is added to the electrolytic cell to detect its concentration.

3. As described in claims 1-2, a method for preparing a self-powered photoelectric sensor based on a CuBi2O4 / MoSe2 composite material, characterized in that: The following steps are involved: S1: CuBi2O4 / MoSe2 composite material was prepared by the following steps: (1) 1 mmol of sodium molybdate and 2 mmol of selenium powder were dissolved in 30 mL of deionized water, and an appropriate amount of citric acid was added. The solution was then stirred and ultrasonicated for 10 min. Finally, the homogeneous solution was transferred to an autoclave and heated at 180°C for 18 hours. The MoSe2 material was obtained by centrifugal washing and drying. (2) Dissolve Bi(NO3)3.5H2O and Cu(NO3)2.3H2O in deionized water and stir them magnetically to dissolve them completely. Add an appropriate amount of NaOH to adjust the pH to 10. Then, add MoSe2 separately while stirring magnetically. Transfer the mixture to a polytetrafluoroethylene-lined autoclave and react at a certain temperature for a period of time. After natural cooling, transfer the solution to a polytetrafluoroethylene-lined autoclave and react at 180°C for 12 hours. After the reaction is completed, wait for the high-temperature autoclave to cool to room temperature, remove the solution from the polytetrafluoroethylene lining, centrifuge at 8000 rpm for washing, and then place it in a vacuum drying oven to dry for 6 hours to finally obtain a CuBi2O4 / MoSe2 heterojunction composite material. S2: Place the ITO conductive glass in acetone, ethanol, and deionized water in turn, and ultrasonically treat for 15 minutes. Then use a hole puncher to punch a 6mm diameter hole in a 1cm×1cm insulating tape and cover the upper half of the cleaned conductive surface of the ITO electrode sheet with it. S3: Weigh 6 mg of the CuBi2O4 / MoSe2 composite material prepared in step S1, add it to 1 mL of deionized water, and ultrasonicate it to disperse it evenly. Take 20 μL of the evenly dispersed CuBi2O4 / MoSe2 suspension and drop it into a 6 mm hole in the insulating tape. Finally, air-dry it naturally to obtain a working electrode.

4. As described in claim 3, a self-powered photoelectric sensor based on a CuBi2O4 / MoSe2 composite material is characterized in that, in step S1, the washing step is: first washing with deionized water, then centrifuging again and washing and discretizing with anhydrous ethanol, and repeating 2 to 3 times.

5. The CuBi2O4 / MoSe2 composite material self-powered photoelectrochemical sensor according to claims 1-4, wherein S3 is specifically: placing a working electrode uniformly containing the CuBi2O4 / MoSe2 composite material in an electrolyte, and using a three-electrode system to prepare a CuBi2O4 / MoSe2 composite material self-powered photoelectrochemical sensor.